Growth and size of stem cells from human exfoliated deciduous teeth cultured in platelet lysate vs. fetal bovine serum for regenerative applications - Ardeshir Talebi; Sanaz Razi; Sahar Talebi; Nosrat Nourbakhsh; Hossein Talebi; Sareh Soroushzadeh; Samin Razi; Seyed Ali Mosaddad (European Journal of Medical Research)
Abstract Background Stem cells from human exfoliated deciduous teeth (SHED) can differentiate into functioning neurons and oligodendrocytes and exhibit immunomodulatory and regenerative properties. This study aimed to compare the growth and size of SHED cultured in human platelet lysate (hPL) and fetal bovine serum (FBS), with the goal of evaluating their potential use in regenerative medicine. Methods Healthy deciduous teeth with uninflamed pulp were used for culture. Growth, proliferation, and morphology of the cultured SHED, as well as the mean surface area, length, and width of the cells, were compared between FBS and hPL. Results The mean surface area of the cultured SHED was lower on FBS than on hPL on days 4, 6, and 9 of passage 0, higher on FBS on day 2, and comparable on days 5 and 10. Comparison of growth, proliferation, and morphology of the cultured SHED on FBS and hPL on days 3 and 9 of passage 0 showed no significant difference. In addition, there was no significant difference regarding growth, proliferation, and morphology of the cells between FBS and hPL on the same days of passages 1, 2, 3, and 4. The total mean length of the cells was lower on hPL than on FBS within 10 days (137.9 vs. 148.1 µm), while the total mean width of the cells was higher on hPL than on FBS within 10 days (28 vs. 26 µm). Conclusions FBS and hPL were comparable regarding growth, proliferation, and morphology of SHED, with higher mean width and lower mean length on hPL than on FBS within 10 days and overall comparable mean surface area after 10 days of passage 0. Therefore, FBS and hPL appear to be relatively similar for the culture of SHED, and hPL can replace FBS for this purpose.